Health facilities readiness in providing non-communicable disease services in Bangladesh - Dana, Gaylan Peyari Tarannum; Afroz, Sawkia (International Journal of Public Health Science (IJPHS), 2022)
The study aims to assess the readiness of health facilities to provide diagnosis and treatment for three specific non-communicable diseases such as diabetes, CVD and CRD related services in Bangladesh. This cross-sectional study used data from the 2017 Bangladesh Health Facility Survey. A total of 406 health facilities providing all three services were considered for this study. The findings of the study illustrated that there were rural-urban disparities in health facilities to provide diabetics, CVD, CRD related services. Diabetics and CRD related services were significantly higher in public health facilities of urban areas compared to rural areas (P <0.008 and P<0.001, respectively). Also, public health facilities of urban areas were more likely to provide CVD related services compared to rural areas. While private health facilities of urban areas were more likely to provide CVD, CRD related services than rural areas. Private health facilities of rural areas were in better condition to provide diabetes-related services than urban areas. Therefore, in order to cope up with the rising burden of diabetes, CVD and CRD and to minimize the burden of disease-specific out-of-pocket healthcare expenses, recommendations include strengthening and improving stewardship, improving quality of services and improving monitoring as well as supervision of decentralized health facilities.